BILL NO. HB 19 AMENDMENT NO. (FOR DRAFTERS USE ONLY) SENATE ACTION HOUSE ACTION (Tufts Archival Research Center, 2007)
Amendment to bill H.B. 19 stating that no person may smoke in a public place or at a public meeting except in designated smoking areas. Discusses penalties in event of violation.